Tanggungjawab Pengelolaan Objek Wisata Terhadap Kecelakaan Wisatawan Didaerah Objek Wisata - Aswad Andika Putra; Muh. Amiruddin (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The results of this study indicate that the management of tourist objects feels that they are based on Regional Regulation No.3 of 2017 concerning the Withdrawal of Retribution for Recreation and Tourism Objects, namely SOP / operational costs are borne by the tourism office, then all entrance fees to tourist attractions, gasebo tickets, and the toilets are deposited daily to the treasurer for the tourism office's income for 24 hours, then from the revenue treasurer deposits to the regional treasury, the tourism office employs honorarium workers who have their respective duties, including working in lockers, guarding the gasebo, and maintaining toilets and other officers who hired as cleaning and security officers, as well as providing paramedics and SAR teams and working with the PM and the police on certain days such as holidays. The form of responsibility given by the manager of a tourist attraction who has an accident will be given health facilities by the tourism office while those who die in the world will be given a grant if they apply for assistance to the tourism office, but only local tourists who have a KTP / KK Bantaeng Regency can receive grant assistance while tourists outside the region are only provided with health facilities.